Educational governance in Nepal: weak government, donor partnership and standardised assessment. Issue 1 (2nd January 2021) - Regmi, Kapil Dev
ABSTRACT: In the context of educational globalisation, the role of supranational organisations in shaping the educational policy decisions, especially of aid-dependent countries, has increased. Using global governance as a theoretical framework and Critical Policy Sociology (CPS) as a methodological framework, this paper analysed key educational policy documents produced by the World Bank (WB) and the Government of Nepal (GON), as well as interviews conducted with 13 key educational planners in Nepal. The analysis found that the nature and scope of educational management has changed because of the shift from traditional government to a new governance mechanism. In this new mechanism, educational governance is shared among international donors, the private sector and the GON. As Nepal's educational policy decisions are increasingly shaped by international donors, educational strategies recommended by them have shaped Nepal's educational policy and planning decisions.